A Prospective Study of Enterococcal Bacteremia in Cancer vs.. Non-Cancer Populations: One Disease, Two Tales. (4th October 2017) - Munita, Jose M; Contreras, German; Sahasrabhojane, Pranoti; Petitto, Gabriela Sanchez; Araos, Rafael; Wanger, Audrey; Aitken, Samuel L; Shelburne, Samuel A; Arias, Cesar
Abstract: Background: Enterococcal bacteremia (EB) affects mainly critically ill, immunocompromised patients and those with catheters or foreign bodies. In particular, patients with hematological malignancies seem to be at high risk of developing EB. The epidemiology of EB affecting cancer vs. non-cancer populations is not clearly studied Methods: We performed a prospective, observational cohort study of adult patients with EB in 2 tertiary hospitals (a general hospital [GH] and a major cancer center [CC]) located in Houston, TX, between September 2016 and March 2017. We included individuals with EB for whom follow-up blood culture data within 7 days of the index culture were available. Microbiologic failure (MF) was defined as clearance of bacteremia ≥ 4 days after the first blood culture. Data were assessed by the Chi-squared and Wilcoxon rank-sum test Results: A total of 116 individual cases of EB were included (47 vs. 69 in the GH and CC, respectively); E. faecalis and E. faecium were the most common species in both institutions, with E. faecalis more frequently isolated in the GH than in the CC (87 vs. 42%; P < 0.0001). In contrast, VRE (all E. faecium ) were more common in the CC than in the GH (16% vs. 6%, respectively). Presence of a line when EB occurred was more frequent in the CC (23 vs. 13%, respectively). Infectious diseases consultation was requested in ca. 75% of cases in both hospitals. Endocarditis occurred in 19% of the cases in the GH but was rare in the CC (1%). Directed therapy with a single agent was the main treatment strategy in the GH compared with the CC (59% vs. 27%; P = 0.001). Ampicillin (AMP) and vancomycin were commonly used as monotherapy in the GH whereas daptomycin (DAP) and vancomycin were drugs of choice in the CC. Combination therapy was used in 36% and 51% in the GH and CC, respectively with AMP + gentamicin and DAP + tigecycline used in GH vs. the CC, respectively. MF did not differ between centers, occurring in in 36% and 25% of the cases in the GH and CC, respectively (P = NS). All cause mortality at 30 days was 11% vs. 30% in the GH vs. CC, respectively ( P = 0.009) Conclusion: Major differences in the epidemiology and management of EB between nearby hospitals were found. Our data indicate that specific stewardship initiatives need to be tailored according to the type of clinical setting when dealing with EB Disclosures: All authors: No reported disclosures.